A predator-prey model for stock market - Zakuan, Nur Afira; Jacob, Kavikumar (Enhanced Knowledge in Sciences and Technology, 2021)
As companies are continuously competing, they are affected because their interaction influences the availability of resources in their development. Besides, this model uses numerical techniques as tools in order to calculate the coefficient of the model. The predator-prey model for the stock market was studied numerically were presented. This study focused on applying the biological mathematical model to the evaluation of behaviour between two companies using a predator-prey model as the basis. Moreover, in this research, equilibrium point, stability, and their periodic solution by the use of Hopf bifurcation were analysed in order to determine the requirement that will ensure the coexistence of both companies or the failure of them or both. Lastly, this study will discuss the two competing companies in the real economy to discover the use of predator-prey models in the stock market specifically and study the values of the parameters that will impact whether the system is a stable or experienced bifurcation.